Clean air policies are key for successfully mitigating Arctic warming - von Salzen, Knut; Whaley, Cynthia H.; Anenberg, Susan C.; Van Dingenen, Rita; Klimont, Zbigniew; Flanner, Mark G.; Mahmood, Rashed; Arnold, Stephen R.; Beagley, Stephen; Chien, Rong-You; Christensen, Jesper H.; Eckhardt, Sabine; et al. (Springer Science and Business Media LLC, 2022)
A tighter integration of modeling frameworks for climate and air quality is urgently needed to assess the impacts of clean air policies on future Arctic and global climate. We combined a new model emulator and comprehensive emissions scenarios for air pollutants and greenhouse gases to assess climate and human health co-benefits of emissions reductions. Fossil fuel use is projected to rapidly decline in an increasingly sustainable world, resulting in far-reaching air quality benefits. Despite human health benefits, reductions in sulfur emissions in a more sustainable world could enhance Arctic warming by 0.8 degrees C in 2050 relative to the 1995-2014, thereby offsetting climate benefits of greenhouse gas reductions. Targeted and technically feasible emissions reduction opportunities exist for achieving simultaneous climate and human health co-benefits. It would be particularly beneficial to unlock a newly identified mitigation potential for carbon particulate matter, yielding Arctic climate benefits equivalent to those from carbon dioxide reductions by 2050. Reduction in key air pollutants, especially particulate carbon, can help mitigate Arctic warming with associated benefits for global climate and human health, according to Earth system model simulations under future emissions scenarios.